Excessive smartphone usage among early adolescents: impact on social competence - Syed Ahmad Muhajir Alhaddad Syed Esa,; Nurul Hudani Md Nawi,; Agnis Sombuling, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The benefit mobile technology brings is not limited to learning and entertainment but it also modifies human aspect of social communication. Despite the high number of previous research available concerning smartphones, there is still a gap of research that needs to be addressed such as its effect towards social competence. As the social system becomes complex, communication technology evolves to ensure the social needs are accomplished. For this study, 236 students aged between 13-14 years old were recruited and given a set of questionnaire which comprised Mobile Phone Problem Use Scale, Social Competence Scale for Teenagers and Self Scoring Self-Control Scale. In this study, the researcher attempted to examine the effect of excessive smartphone usage on social competence with self-control as mediator. Regression analysis was used to estimate the effect between the variables. The result indicates that there is negative relationship between excessive smartphone usage and social competence. However, when self-control is tested in the model as a mediator, excessive smartphones usage was not prevalent to predict social competence. This concludes to the apparent role of self-control as a mediator. The implication of study has contributed to the practical importance and methodological aspect of studies involving social competence and self-control.